(untitled) (FAVE Sección Ciencias Veterinarias, 2025)
Academic progress depends on grade-by-grade progress. Low graduation rates question the effectiveness of educational policies. In the career of Veterinary Medicine at the National University of Rosario (UNR) Argentina, the average duration to graduate is seven to nine years, evidencing the need to implement strategies to improve student performance. The aim of this study was to analyze the period between obtaining regularity and passing the final exam in the course of Dairy Cattle Production (DCP) at the Faculty of Veterinary Sciences (FVSc) of the UNR. Retrospective data of students who attended the academic years between 2016 and 2024 obtained from the records of the SIU-guaraní system of the FVSc-UNR were used. The following variables were analyzed: regular students (AR), students approved as of January 2025, students who have not yet passed as of January 2025, % of students approved as of January 2025, Interval regularization - approval (IR-A1) in days, Interval regularization - approval (IR-A2) in days, Interval regularization - approval (IR-A3) in days. It is concluded that the time between regular attendance and passing the final exam (IR-A1 and IR-A2) for the DCP subject at FVSc ranged from 8 to 12 months for the years analyzed. Furthermore, between 22 and 27 months after the subject was regularized, only 50% of students passed (IR-A3).